2016
DOI: 10.1002/jor.23203
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of micro‐motion to backside wear in a fixed bearing total knee arthroplasty

Abstract: This study seeks to identify important factors related to backside wear of tibial inserts in vivo and determine an appropriate wear model for backside wear. An IRB approved database was queried for tibial inserts of a single design from one manufacturer that exhibited evidence of rotatory motion on the backside of the polyethylene. These devices were measured for volumetric wear using a previously established protocol. Features including the change in locking lip width and measurement of micro-motion marks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Using mathematical models of PE wear and data from retrievals, Levine et al. (2016) demonstrated that multidirectional micromotions (which result in arcuate patterns similar to those observed in NexGen knees) play a critical role in backside wear. Our SEM findings—which suggested differences in the extent of micromotion between designs—were confirmed by Bhimji et al.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Using mathematical models of PE wear and data from retrievals, Levine et al. (2016) demonstrated that multidirectional micromotions (which result in arcuate patterns similar to those observed in NexGen knees) play a critical role in backside wear. Our SEM findings—which suggested differences in the extent of micromotion between designs—were confirmed by Bhimji et al.…”
Section: Discussionmentioning
confidence: 96%
“…2012, Levine et al. 2016). Measurement using micro CT is very precise, but it requires complex equipment, custom software, and time-consuming data processing—and has therefore been used in studies involving a much smaller number of samples than in our material (Crowninshield et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paxton et al [56] found a similar risk of revision for highly crosslinked polyethylene compared with conventional polyethylene. Highly crosslinked polyethylene is rarely used in Norway in knee arthroplasty (8% in 2013-2015) [69], indicating improvements in conventional polyethylene and polishing, sterilization, and locking mechanisms [37,39,68]. The risk of revision resulting from malalignment was unchanged for TKA and UKA.…”
Section: Changes In Revision Causesmentioning
confidence: 99%
“…Although the interference fit of fixed-bearing TKR with locking mechanism was included in functional knee simulator testing of the tibial insert, 10,11 it is rare to investigate the effect of interference fit on articular and backside wear rates of the tibial insert. Compared with retrieval studies and wear testing, finite element analysis (FEA) is an attractive alternative for parametric studying the influence of interference fit between the tibial insert and the tibial tray without expensive experimental cost.…”
Section: Introductionmentioning
confidence: 99%